HLA‐B50 polymorphism in the Saudi population. (21st November 2013) - Jawdat, D.; Al‐Hamad, B.; Al‐Jumah, M.; Hajeer, A.
Summary The HLA‐B50 serologic family is very frequent in people of Arabic origin. In Saudi Arabia, HLA‐B50 is the most frequent HLA‐B allele. The aim of this study was to investigate the distribution of HLA‐B50 alleles in healthy Saudi individuals. A total of 162 healthy Saudi individuals were selected based on low‐resolution HLA typing. DNA samples were typed by sequence‐based typing method for exons 2, 3 and 4 of the HLA‐B locus (Genome Diagnostics B.V.). The HLA‐B*50 alleles were analysed using SBT engine software. HLA‐B*50:01:01 was found in 161 of 162 individuals (99.4%), while HLA‐B*50:09 was found in one individual (0.6%). HLA‐B*50:01:01 is the most common HLA‐B50 allele in Saudi Arabia.